Penyalahgunaan Narkoba di Kalangan Remaja dan Cara Mengatasinya di SMK 3 Kota Sukabumi (KANGMAS: Karya Ilmiah Pengabdian Masyarakat, 2023)
The drug problem in Indonesia remains urgent and complex. Over the last decade, this problem has become widespread. This is evidenced by a significant increase in the number of addicts or drug addicts and an increase in the disclosure of drug-related criminal cases. The patterns are getting more diverse and the syndicate network is getting bigger. Indonesian society, even the global community, is currently in a very alarming situation due to the widespread and widespread use of various types of illegal drugs. This concern is exacerbated by the illicit trafficking of drugs that has spread to all levels of society, including the younger generation. This will have a major impact on the country and the nation's life in the future. The behavior of some teenagers who seem to ignore the values, norms and laws that regulate people's lives is one of the causes of the widespread use of drugs among the younger generation. Therefore, it is necessary to use qualitative research methodologies with observational surveys and direct interviews with school principals using data primary. With rare steps that are required together with the local government for high school students, especially SMK 3 SUKABUMI CITY, where the purpose of this community service is to minimize drug abuse among teenagers and further provide socialization of drug abuse among teenagers and how to overcome it for SMK 2 Sukabumi in motivating students not to abuse drugs. The next plan was to provide socialization to the students of SMK 3 SUKABUMI CITY, the second plan was carried out together with the SIP 51 Serdiks and the National Police Education and Training Center.